SISTEM PAKAR UNTUK DIAGNOSA KERUSAKAN PADA SMARTPHONE ANDROID MENGGUNAKAN METODE FORWARD CHAINING - Aldo Airlangga; Achmad Zakki Falani (SPIRIT, 2022)
An expert system is a program that computerizes reports that try to imitate the thought processes and knowledge of experts in solving problems. Along with the development of time, expert systems make it easier for the public to diagnose a disease or damage. Reported from the statcounter.com page, Android users in Indonesia in 2020 reached 91.85%. This number can still increase considering the number of smartphone prices that are increasingly affordable and sophisticated. The number of android smartphones that are used will cause problems in the form of damage to android smartphones caused by factory errors or errors from the user himself. But in general, people do not know much about the right solution to overcome the damage and choose to buy a new cellphone. In this study, an expert system will be implemented to diagnose damage to an Android smartphone using a web-based forward chaining method to assist the public in diagnosing damage to their Android smartphone. The results of this expert system can be used as a reference in estimating the cost of damage to an android smartphone.